THE INFLUENCE OF SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF THE PERSONALITY OF A MILITARY ON HIS PERCEPTION OF RISK AND PSYCHOLOGICAL READYNESS FOR IT - Safin, O.; Mas, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article presents the results of a study of the impact of socio-psychological characteristics of the serviceman's personality on his perception of risk and psychological readiness for risky behavior. It is noted that the individual's perception of risk is a complex structural formation that reflects the individual's attitude to risk as a socially significant object and is associated with psychological readiness for risky behavior. Social perceptions of risk are interrelated with personal willingness to take risky behaviors. The type of psychological readiness for risky behavior is determined by the prevailing social imaginations about risk. The study identifies the main types of psychological readiness for risk: "risk as a tool for material gain", "risk as overcoming their own physical and psychological capabilities", "risk as a sign of trust". Psychological readiness for risk and attitude to it are related to the socio-psychological characteristics of the soldier's personality. High levels of motivation to achieve, self-actualization, personal creativity and high self-esteem imply a higher psychological willingness to take risks. Psychological readiness for risk, as well as motivation for it are determined by the socio-psychological adaptability of the serviceman. A high level of adaptability implies a more pronounced psychological readiness for risky behavior. Adapted servicemen show a higher level of psychological readiness for risk for the sake of "prestige" and "interest", while servicemen with low socio-psychological adaptation are less willing to take risks, and in cases of choice are dominated by motives to avoid trouble and material rewards.
Keywords: risk; psychological readiness, personality, serviceman, imagination